Exploring the Influence of Oral Health on Pregnancy Outcomes: A Narrative Review - Muhammad Mohsin Javaid; Samina Naeem Khalid; Shahzad Ali Khan; Hina Nasim; Mudassar Mushtaq Jawad Abbasi; Shahzad Ahmad; Shazia Iqbal; Muhammad Farooq Umer (Global Health, Epidemiology and Genomics)
Oral health significantly impacts overall health, with increasing evidence linking poor oral health to adverse pregnancy outcomes. Periodontal disease, a chronic gum condition, is associated with preterm birth, low birth weight, and preeclampsia. Systemic inflammation and bacterial translocation are proposed mechanisms connecting periodontal disease to pregnancy complications. Maternal immune responses may be impaired, increasing systemic inflammation, and triggering preterm labor. In addition, oral bacteria may reach the uterus, causing localized inflammation and poor outcomes. Intervention trials show mixed results—some small studies report improved birth outcomes after periodontal treatment, while larger trials show no significant effect. These discrepancies highlight the need for further research on patient subgroups, disease categories, and treatment strategies. Prenatal care should emphasize preventive dental care, including regular checkups, good oral hygiene, and treatment of periodontal disease. Addressing oral health during pregnancy can improve outcomes for both mother and child. Future studies should explore the oral-systemic connection, host susceptibility, and effective interventions for at-risk individuals. Comprehensive oral health care during pregnancy offers the potential to reduce adverse outcomes and promote better maternal and fetal health.